Performance effectiveness of teachers in the agricultural colleges of Kerala Agricultural University - Mercy Bella M (Department of Agricultural Extension, College of Agriculture, 2006)
The study entitled “Performance effectiveness of teachers in the agricultural colleges of Kerala Agricultural University” was undertaken to assess the performance effectiveness of teachers. It also aimed to delineate the factors that influencing the performance effectiveness of teachers and also to identify the constraints to make suggestion for enhancing their performance effectiveness.